2011
DOI: 10.1117/12.874362
|View full text |Cite
|
Sign up to set email alerts
|

Numerical optimization of periodic hole arrays for plasmonic Raman sensor

Abstract: A plasmonic Raman sensor using periodic hole arrays was investigated numerically and experimentally. In previous work, we fabricated a hole array in a thin metal film on a dielectric substrate using focused ion beam lithography and succeeded in observing surface plasmon resonance. Those experimental results agreed well with simulation results (for an array of cylindrical holes) obtained using the finite-difference time-domain method. However, a cylindrical hole array provides insufficient sensitivity (i.e., el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…This is mainly due to the effect of the beam (aspect ratio) used in fabricating the holes (i.e., producing a tapered hole shape). We demonstrated the effectiveness of hole shape dependency (i.e., cylindrical or tapered hole structures) for electric field enhancement, transmittance, and reflectance spectra obtained by numerical simulation using the FDTD method [23]. We found that the experimental transmittance spectra agreed very well with the calculated ones, and the electric field intensity was enhanced by using tapered holes.…”
Section: Introductionmentioning
confidence: 81%
“…This is mainly due to the effect of the beam (aspect ratio) used in fabricating the holes (i.e., producing a tapered hole shape). We demonstrated the effectiveness of hole shape dependency (i.e., cylindrical or tapered hole structures) for electric field enhancement, transmittance, and reflectance spectra obtained by numerical simulation using the FDTD method [23]. We found that the experimental transmittance spectra agreed very well with the calculated ones, and the electric field intensity was enhanced by using tapered holes.…”
Section: Introductionmentioning
confidence: 81%